Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
- p = 0
Step-by-step explanation:
Given expression:
- - 10p + 3(8 + 8p) = -6(p - 4)
Solving for p:
- -10p + 24 + 24p = -6p + 24
- 14p + 24 = -6p + 24
- 14p + 6p = 24 - 24
- 20p = 0
- p = 0
Answer:
Step-by-step explanation:
here you go mate
step 1
- 10p + 3(8 + 8p) = -6(p - 4) equation
step 2
- 10p + 3(8 + 8p) = -6(p - 4) simplify by distributing
14p+24=-6p+24
step 3
14p+24=-6p+24 subtract 24 from each sides
20p=0
step 4
20p/20=0/20 divide both sides by 20
answer
p=0
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.